Synthesis and Characterization of New Optically Active Copolyamides Based on N-Phthaloyl-L-Glutamic Acid, Terephthalic, Fumaric and Adipic Acids - Faghihi, Kh.; Heidari, P.; Shabanian, M. (Asian Journal of Chemistry, 2012)
Six new copolyamides (9a-f) were synthesized by direct polycondensation reaction of N-phthaloyl-L-glutamic acid (3) with 4,4'-diamino diphenylether (4), 4,4'-diamino diphenylsulfone 5 in the presence of adipic acid (6), fumaric acid (7) and terephthalic acid (8) as a second diacid in a medium consisting of N-methyl-2-pyrrolidone, triphenyl phosphite, calcium chloride and pyridine. N-phthaloyl-L-glutamic acid (3) was synthesized by reaction of phthalic anhydride (1) with L-glutamic acid (2) in acetic acid solution. The resulting polymers were characterized by means of FTIR spectroscopy, elemental analyses, inherent viscosity and specific rotation. Phthalimide rings as a bulky pendent group in the polymer chains disturb interchain and intrachain interactions and make these PAs readily soluble in polar aprotic solvents such as N,N-dimethyl acetamide, N,N-dimethyl formamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone and solvents such as sulfuric acid. Thermal properties of these polymers were investigated using thermal gravimetric analysis and differential thermal gravimerty.